Native language maintenance among bilingual immigrants in Lima: linguistic and ethnic loyalty in two urban-marginal communities - Quesada Castillo, Félix (2011)
This article reports the results of a searching on the sociolinguistic phenomenon of native language maintenance (Fishman, 1965 and 1968) in a special situation of urban bilingualism. The aforementioned effect is given as maintenance of loyalty to the vernacular and maternal ancestral ethnic loyalty. The research universe is made up of bilingual of Gosen City (Villa María del Triunfo) and Pamplona Alta (San Juan de Miraflores), communities made up ofbilingual Quichua-Castilian, Aymaracastilian and monolingual Castilian. The study of native language maintenance in a singular situation gives us an adequate empirical knowledge ofthe phenomena that are generated in the vernacular language contact and Castilian as the language of the dominant culture. Furthermore, the result ofthis investigation will aids the sociolinguistic basis for the development and implementation of language and education policies for the benefit of those communities. In this regard, research is not restricted to the discussion of theoretical aspccts of sociolinguistics, but also has implications for language policy in order to form an inclusive and equitable society.